In vitro immunoreactivity and in vivo neutralization of Trimeresurus gracilis venom with antivenoms targeting four pit viper species. - Po-Chun Chuang; Jia-Wei Chen; Yuen-Ying Chan; Tsz-Chun Tse; Yu-Wei Chiang; Tein-Shun Tsai (Public Library of Science (PLoS), 2024)
Snakebite envenomation is a significant global health issue that requires specific antivenom treatments. In Taiwan, available antivenoms target a variety of snakes, but none specifically target Trimeresurus gracilis, an endemic and protected species found in the high mountain areas of Taiwan. This study evaluated the effectiveness of existing antivenoms against T. gracilis venom, focusing on a bivalent antivenom developed for Trimeresurus stejnegeri and Protobothrops mucrosquamatus (TsPmAV), as well as monovalent antivenoms for Deinagkistrodon acutus (DaAV) and Gloydius brevicaudus (GbAV). Our research involved in vivo toxicity testing in mice and in vitro immunobinding experiments using (chaotropic) enzyme-linked immunosorbent assays, comparing venoms from four pit viper species (T. gracilis, T. stejnegeri, P. mucrosquamatus, and D. acutus) with three types of antivenoms. These findings indicate that TsPmAV partially neutralized T. gracilis venom, marginally surpassing the efficacy of DaAV. In vitro tests revealed that GbAV displayed higher binding capacities toward T. gracilis venom than TsPmAV or DaAV. Comparisons of electrophoretic profiles also reveal that T. gracilis venom has fewer snake venom C-type lectin like proteins than D. acutus, and has more P-I snake venom metalloproteases or fewer phospholipase A2 than G. brevicaudus, T. stejnegeri, or P. mucrosquamatus. This study highlights the need for antivenoms that specifically target T. gracilis, as current treatments using TsPmAV show limited effectiveness in neutralizing local effects in patients. These findings provide crucial insights into clinical treatment protocols and contribute to the understanding of the evolutionary adaptation of snake venom, aiding in the development of more effective antivenoms for human health.